Platelet procoagulant potential is reduced in platelet concentrates ex vivo but appears restored following transfusion. Issue 12 (5th October 2021) - Tohidi‐Esfahani, Ibrahim; Tan, Shereen; Tan, Chuen Wen; Johnson, Lacey; Marks, Denese C.; Chen, Vivien M.
Abstract: Background: The procoagulant profile of platelet concentrates (PCs) following transfusion has been difficult to evaluate due to lack of specific markers. This study aimed to characterize procoagulant platelets in PCs and the effect of transfusion. Study design and methods: Buffy coat‐derived PCs from 12 donors were pooled, split, then stored conventionally, cold (2–6°C) or cryopreserved (−80°C). Procoagulant platelet profiles were assessed by flow cytometry (GSAO + /P‐selectin + ), lactadherin‐binding, and calibrated automated thrombogram, during storage, unstimulated, or after thrombin and collagen stimulation and compared with blood from healthy volunteers. Platelet activation (P‐selectin) and procoagulant platelet formation potential were measured (flow cytometry) in patients receiving clinically indicated conventional PC transfusion. Results: Independent of significant increases with storage, procoagulant platelet proportions with and without agonist stimulation were significantly blunted in conventionally stored PCs (stimulated day 5 conventional PC 4.2 ± 1.3%, healthy volunteer blood 11.1 ± 2.9%; p < .0001). Cryopreserved PCs contained the highest proportion of procoagulant platelets (unstimulated: cryopreserved 25.6 ± 1.8% vs. day 5 conventional 0.5 ± 0.1% vs. day 14 cold‐stored 5.8 ± 1.0%, p < .0001), but demonstrated minimal increase with agonist. Transfusion of PCs was associated with an increase in procoagulant platelets (2.2 ± 1.4% vs. 0.6 ± 0.2%; p = .004) and reversal of the blunted agonist response (15.8 ± 5.9% vs. 4.0 ± 1.6%; p < .0001). Procoagulant responses post‐transfusion were significantly higher than healthy controls, suggesting a priming effect. The P‐selectin agonist response was not restored upon transfusion (79.4 ± 13.9% vs. 82.0 ± 2.5%). Conclusion: Storage blunts the procoagulant platelet response to agonist stimulation in PCs. Despite this, conventionally stored PCs have high procoagulant potential following transfusion, with a discordant, persistent reduction in P‐selectin response.